The Potential of CALL and the Task-Based Approach to Prevent and Reverse Interlanguage Fossilisation - Alharbi, Jamilah Maflah (Journal of Ecohumanism, 2024)
Purpose: This study reviews how different teaching approaches may effectively address interlanguage fossilisation with the techniques and characteristics of these approaches. To these aim a task-based approach and a computer-mediated approach to learning will be analysed to review how they address the following factors that are believed to cause interlanguage fossilisation. Research Method: This study will use a qualitative strategy to review how different teaching approaches may effectively address interlanguage fossilisation with the techniques and characteristics of these approaches. To these aim a task-based approach and a computer-mediated approach to learning will be analysed to review how they address the following factors that are believed to cause interlanguage fossilisation. Findings: It would seem that an approach that combines task-based learning together with the methods that CALL provides would not only not be incompatible, but it can also provide the learners with more opportunities to either avoid interlanguage fossilisation, or even reverse its effects. This paper has reviewed the advantages that both approaches have in tackling a variety of factors that affect interlanguage fossilisation. In this case, it is clear that both approaches provide opportunities for the learners to receive corrective feedback, as well as explicit instruction on those structures that are fossilised. It is worth noting that instructors need to work case by case on the students to tailor the approach to their needs. In addition, both a task-based learning approach as well as CALL require the provision of sufficient input that is rich and suitable for the learner in order to avoid or tackle fossilisation. One of the most challenging aspects of both teaching approaches towards fossilisation is the provision of instruction that caters for socio-emotional factors affecting the learners. It would appear that this is challenging for all approaches as it is hard to help students adapt to the TL culture and identify with the language within a classroom environment.